Excision margins and sentinel lymph node status as prognostic factors in thick melanoma of the head and neck: A retrospective analysis. Issue 9 (25th March 2016) - Ruskin, Olivia; Sanelli, Alexandra; Herschtal, Alan; Webb, Angela; Dixon, Ben; Pohl, Miklos; Donahoe, Simon; Spillane, John; Henderson, Michael A.; Gyorki, David E.
ABSTRACT: Background: Recommended margins for thick cutaneous melanoma (Breslow thickness >4 mm; T4) have decreased over recent decades. Optimal margins and the role of sentinel node biopsy (SNB) in thick head and neck melanoma remain controversial. Methods: A single‐center review was conducted of patients treated between 2002 and 2012 assessing the impact of excision margins and sentinel lymph node status on locoregional recurrence and melanoma‐specific survival (MSS). Results: One hundred eight patients were identified. Median age was 71.1 years and median Breslow thickness was 6.0 mm. Median follow‐up was 40 months. Locoregional recurrence occurred in 27% and there was no significant reduction in recurrence with margins ≥2 cm ( p = .17). Increasing margins did not improve survival ( p = .58). Fifty‐nine patients (55%) underwent SNB, of which 27% were positive. There was a trend toward longer survival for patients who were sentinel lymph node‐negative ( p = .097). Conclusion: Wider margins do not significantly improve locoregional recurrence or MSS. Sentinel lymph node involvement reflects a poor prognosis. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1373–1379, 2016